Intelligence: A very short introduction - Deary, Ian J. (Oxford Oxford university press, 2001)
For people with little or no knowledge of the science of human intelligence, this volume takes readers to a stage where they are able to make judgments for themselves about the key questions of human mental ability. Each chapter addresses a central scientific issue but does so in a way that is lively and completely accessible. Issues discussed include whether there are several different types of intelligence, whether intelligence differences are caused by genes or the environment, the biological basis of intelligence levels, and whether intelligence declines as we grow older.